Justification for automobile transportation technology of limited coal shipments in the city - E. E. Vitvitsky; N. I. Yurieva; G. O. Tazhigulova; S. G. Kurymbaev; P. U. Baigozhina (Вестник СибАДИ, 2022)
Introduction. In the economy of states, one of the constant tasks remains to ensure the urgent needs of the population, in an autumn-winter period in cities and settlements, the task of providing fuel (coal) to households is highlighted. The demand for coal is limited by solvency and distributed over the entire period of negative air temperatures. Hence, the supply of coal for the period of heating of dwellings is formed, in many cases, by purchasing lots of coal, representing a share of the total demand during the specified period. The purpose of this work is to find reasonable answers on the use of transportation technologies for limited shipments of goods in cities.Materials and methods. The solution to the problem was carried out within the framework of operational planning for the transportation of limited shipments of coal for the population throughout the city on the basis of the concept of an approach to building a general theory of truck systems functioning for motor transport shipping network, using a regulatory approach when calculating transportation costs, descriptive models of the car’s operation in micro- and delivery motor transport shipping network.Results. Through mathematical modelling, reasonable values of operational plans for the transportation of limited shipments of coal in cities by machine technology and delivery were obtained. Regulatory approach to cost calculation, electronic database of road transport industry updated at the date of calculation. Software and mathematical support for calculating the costs of cargo transportation as part of models of micro and especially small motor transport systems made it possible to reliably determine the planned values of transportation costs by machine technology and delivery.Discussion and conclusion. The advantage of using delivery technology in the conditions under consideration has been established, when transporting coal by road using the case of a city.